Pengalaman Pembelajaran Pendidikan Agama Kristen dengan Menggunakan Teknologi Pembelajaran Quizizz - Juliana Pontoan; Kevin Samuel Kamagi (UKI Press, 2023)
Technology has an important role in the learning process because it can make learning activities more effective and meaningful. Christian religious education is expected to be able to provide learning that can be felt pleasant by students. Therefore, Christian religious education must adjust in terms of methods and means in providing learning in the current technological era. The research method used is descriptive qualitative method. The purpose of this writing is to obtain information about the experience of using the Quizizz application in learning Christian religious education in the church. The research subjects were GKKD Jakarta youth. The results of the study show that Quizizz technology is the choice of learning media for Christian religious education because the Quizizz application can be used in learning Christian religious education in youth because it is easily accessible, makes the learning atmosphere fun, youth is enthusiastic about taking quizzes, can pay attention to lessons, review material that has been studied.